Keberadaan Plankton sebagai Indikator Pencemaran - Lina Rosanti; Arman Harahap (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the level of pollution that occurs in the Barumun River area by identifying the composition of plankton diversity in the river. The method used is a survey method. Sampling was carried out by purposive sampling at three location points with different conditions in the surrounding area based on specific objectives with the researcher's considerations. The results showed differences in plankton density at each observation station, with the highest plankton species diversity value found at station II (1.86) and the lowest plankton species diversity value appearing at station III (1.06). In conclusion, the waters of the Barumun River are categorized as moderately polluted waters. Keywords: Indicator, Pollution, Plankton, Barumun River